Enhancing Critical Thinking Skills in Students: A Study on the Effectiveness of Group Counselling Strategies Using the Talking Stick - Herawati, Anna Ayu; Syahriman, Syahriman; Saputra, Adif Jawadi; Mishbahuddin, Arsyadani; Habibi, Ahmad Syaf Ya (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2023)
Critical thinking skills are a crucial aspect of education aimed at equipping students with strong analytical abilities, deep understanding, and effective problem-solving skills. The primary objective of this study is to assess the impact of implementing the talking-stick-playing strategy during group guidance sessions on the enhancement of critical thinking skills among students majoring in Guidance and Counseling at Bengkulu University. The research methodology employed in this investigation is experimental, utilizing a one-group pretest-posttest design. Participant selection involved purposive sampling, with a sample size of eight students from 29 students. Data collection used the critical thinking ability scale adapted from Purnomo (2020), comprising 5 dimensions and 15 statement items. Analytical techniques were using descriptive analysis and Wilcoxon test analysis. Findings from the descriptive analysis reveal that students' critical thinking abilities were categorized as sufficient before the intervention, but improved to a good level after the treatment. Furthermore, the Wilcoxon test results yielded an Asymp. Sig. (2-tailed) value of 0.000, indicating that the implementation of the talking-stick strategy during group guidance sessions significantly influences the development of students' critical thinking skills. This indicates that the structured and participatory communication method introduced through the Talking-Stick helps students develop their critical thinking skills. Therefore, this approach should be considered by educators and counsellors as a valuable resource in enriching students' learning experiences in higher education.